Antimicrobial Hypochlorous Wound Irrigation Solutions Demonstrate Lower Anti-biofilm Efficacy Against Bacterial Biofilm in a Complex in-vitro Human Plasma Biofilm Model (hpBIOM) Than Common Wound Antimicrobials - Rembe, Julian-Dario; Huelsboemer, Lioba; Plattfaut, Isabell; Besser, Manuela; Stuermer, Ewa K. (Frontiers in Microbiology, 2020)
Biofilms pose a relevant factor for wound healing impairment in chronic wounds. With 78% of all chronic wounds being affected by biofilms, research in this area is of high priority, especially since data for evidence-based selection of appropriate antimicrobials and antiseptics is scarce. Therefore, the objective of this study was to evaluate the anti-biofilm efficacy of commercially available hypochlorous wound irrigation solutions compared to established antimicrobials. Using an innovative complex in-vitro human plasma biofilm model (hpBIOM), quantitative reduction of P. aeruginosa, S. aureus and Methicillin-resistant S. aureus (MRSA) biofilms by three hypochlorous irrigation solutions (two <0.08% and one 0.2% NaClO) were compared to a 0.04% polyhexanide (PHMB) irrigation solution and 0.1% octenidine-dihydrochloride/phenoxyethanol (OCT/PE). Efficacy was compared to a non-challenged planktonic approach as well as with increased substance volume over a prolonged exposure (up to 72 hours). Qualitative visualisation of biofilms was performed by scanning electron microscopy (SEM). Both reference agents (OCT/PE and PHMB) induced significant biofilm reductions within 72 hours, whereby high volume OCT/PE even managed complete eradication of P. aeruginosa and MRSA biofilms after 72 hours. The tested hypochlorous wound irrigation solutions achieved no relevant penetration and eradication of biofilms, despite increased volume and exposure. Only 0.2% NaClO managed a low reduction under prolonged exposure. The results demonstrate that low-dosed hypochlorous wound irrigation solutions are significantly less effective than PHMB-based irrigation solution and OCT/PE, thus unsuitable for biofilm eradication on their own. The used complex human plasma biofilm model thereby mimics the highly challenging clinical wound micro-environment providing a more profound base for future clinical translation.